Answer: six square root of five minus four square root of fifteen
In symbolic form the answer looks like [tex]\boldsymbol{6\sqrt{5} -4 \sqrt{15}}[/tex]
==========================================================
Work Shown:
[tex]\sqrt{5}\left(6 - 4\sqrt{3}\right)\\\\\sqrt{5}\left(6\right) + \sqrt{5}\left(-4\sqrt{3}\right)\\\\6\sqrt{5} -4 \sqrt{5*3}\\\\6\sqrt{5} -4 \sqrt{15}\\\\[/tex]
The basic idea is to distribute the outer term [tex]\sqrt{5}[/tex] to each term inside. From there you simplify.
For the second to last step, I used the rule that [tex]\sqrt{A}*\sqrt{B} = \sqrt{A*B}[/tex]